A rare but important adverse event associated with adult voluntary medical male circumcision: prolonged bleeding - Galukande, Moses; Kahendehe, Carol; Buuza, Eria; Bbaale Sekavuga, Denis (International journal of emergency medicine, 2015)
The majority of bleeding disorders worldwide are undiagnosed. Their moderate or severe forms are associated with considerable morbidity and mortality. In the advent of mass male circumcision for the partial prevention of HIV, undiagnosed and diagnosed cases of bleeding disorders are likely to be increasingly encountered. The ability to screen, diagnose, and manage these cases appropriately will mitigate associated adverse events. We describe three cases of prolonged bleeding after adult voluntary medical male circumcision (VMMC) and propose program measures. Methods: A descriptive case series at tertiary urban hospital serving a VMMC program. The cases were recruited consecutively over a 3-year period. Standard laboratory tests were used to confirm diagnosis. Written informed consent was obtained from each subject. Results: Three cases were described of previously undiagnosed hemophilia A males circumcised during routine VMMC service delivery. They had presented with complaints of prolonged (non-stop or recurring) bleeding. They were aged 16, 22, and 24 years, of low socioeconomic background, with limited formal education. Whereas two of the three were aware of a tendency to prolonged bleeding from minor cuts, they did not volunteer these histories. The patients were referred to a hospital with the resources to test and administer recombinant factor VIII in Kampala (the capital city) 3, 9, and 16 days after circumcision. Two had received whole blood transfusions enroute to this hospital. All three were diagnosed with mild or moderate hemophilia A. Factor IX levels were all within normal range. In all three cases, the bleeding stopped within hours of the initial factor VIII infusion, and two to three maintenance doses were given over the subsequent 2 to 3 days for each patient. Conclusions: Sensitization of health workers in safe male circumcision (SMC) programs for pre-operative diagnosis and appropriate referral is highly recommended.
Keywords: Prolonged bleeding; Voluntary medical male circumcision; Adverse events; Hemophilia